Covid-19 and movement control order: stress and coping strategies of students observing self-quarantine - Adam Andani Mohammed; Md Sayed Uddin; Abdallah Mpawenimana Saidi (Human Resource Management Academic Research Society (HRMARS), 2020)
Coronavirus Disease 2019 (COVID-19) led students feel anxious with a constant internal dialogue of ‘Am I safe?’ that may take a serious toll on their psyche. The self-quarantine and physical distancing, economic hardship and fears of contracting the disease are likely sources of stress. Quite apart, students may also experience both physical sufferings and mental stress due to the news of increasing number of infected cases and reported deaths across the globe. A range of expert guidelines have been developed by governments and health authorities to curtail the spread of the virus. This study models a position paper which persuades the reader to realize that the opinions expressed are valid and could be defended. In gathering supporting evidence, an online qualitative survey was conducted to examine the stress of students observing selfquarantine and physical distancing in and around Desa Ilmu and Unigardern in Kota Saramarahan as well as in apartments at Jalan Kingfisher Sabah. These students were invited as respondents in this online investigation using interview protocol to take their responses. This study is among the first to examine the stress and coping strategies of students observing self-quarantine and physical distancing. The paper may provide useful information about how students cope in stressful situations and also identify effective ways to manage people during distress times in future.